Dinamika Proses Produksi Animasi Independen: Studi Kasus Animasi Cuko Boy sebagai Representasi Budaya Lokal - Fitria, Suci; Fera Indasari; Muslimin Ritonga (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
This study aims to analyze the dynamics of independent animation production and the representation of local culture in the animation Cuko Boy. The background of this research is based on the growth of the independent animation industry in Indonesia, which faces various limitations yet is capable of producing creative works rooted in local identity. This research employs a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, observation, and documentation of the production process of Cuko Boy. The data were analyzed using John T. Caldwell’s Production Culture theory and Ferdinand de Saussure’s semiotic approach to examine the relationship between signifier and signified in representing Palembang’s local culture. The results show that the dynamics of independent animation production are characterized by role flexibility, limited resources, and adaptive creative strategies that utilize local culture as a primary identity. The representation of Palembang’s local culture in Cuko Boy is reflected through visual, linguistic, and symbolic elements, such as city icons, traditional cuisine, and local dialect. This study concludes that independent animation is not only a form of entertainment but also a medium for cultural representation and a creative strategy to overcome industrial limitations.